Characteristics and main controlling factors of dolomite reservoirs in Fei-3 Member of Feixianguan Formation of Lower Triassic, Puguang area - Wang, Shenjian; Xu, Guosheng; Hou, Yingling; Zhuang, Wenjie; Chen, Guomin; Wang, Wei; Wang, Xinyi; Bi, Jianxia; Huang, Changbing; Liu, Qing; Zhuang, Qiuchan; Luo, Qing (Open Geosciences, 2024)
In recent years, studying dolomite diagenesis and controlling factors of reservoir development from microscopic perspective has become a hot subject in deep carbonate gas exploration. In this study, we have carried out a fine classification of different types of dolomite reservoirs in the Fei-3 Member of the Lower Triassic Feixianguan Formation in the Puguang area, and the distribution law and main controlling factors of dolomite reservoirs have been clarified. The results show that the dolomite reservoirs of the Fei-3 Member in the Puguang area include three rock types: residual structure dolomite, microbial dolomite, and crystalline dolomite, and the main reservoir space types are intergranular pores, solution pores/caves, and inter-crystalline pores, respectively, and the solution fractures are mainly developed in the residual structure and microbial dolomites. Most of the dolomite reservoirs are distributed in the Fei 3 sub-member, and the residual structure dolomite is mainly distributed in the relative paleomorphic highs of the Fei 3 sub-member; microbial dolomite is mainly developed in the platform environment with shallow water and intermittent exposure, and is controlled by the growth conditions of microorganisms; the crystalline dolomite is mostly distributed in the relatively shallow water and relatively limited dolomite flat environment. On the plane, the dolomite reservoirs are distributed in the form of clumps. The distribution of residual structure dolomite reservoir is controlled by paleotopography and early exposure corrosion. Microbial dolomite is formed in the microbial mat microfacies, and the distribution range of microbial mat controls the development of microbial dolomites. The diagenetic types of the dolomites in the target layer include dolomitization, dissolution, rupture, and material filling. Various kinds of pores formed by syngenetic dissolution provide channels for later buried dissolution, and organic acids formed by organic matter maturation under deep burial conditions play a crucial role in dissolution of dolomite and promote the formation of dissolution pores. In the burial stage, hydrocarbons enter the dolomite, which can effectively prevent the growth of late authigenic minerals, thus promoting the preservation of pores. The structural fracture system formed by late tectonic movement can communicate with different pore groups and improve the reservoir quality.